Mitigation of climate change with biomass harvesting in Norway spruce stands: are harvesting practices carbon neutral? - Mäkipää, Raisa; Linkosalo, Tapio; Komarov, Alexander; Mäkelä, Annikki (NRC Research Press, 2015)
Biomass combustion is considered to be carbon neutral, but intensive biomass harvesting may negatively impact carbon stocks in forest soil and vegetation, which can offset the benefits of substituting fossil fuels with biomass. Here we evaluated conventional stem-only harvesting, whole-tree harvesting (WTH), and WTH excluding needles in terms of timber yield, biomass harvests, and forest carbon sequestration. We simulated harvest scenarios in current and changed climates with a process-based growth model (PipeQual) that was integrated with models describing soil decomposition (ROMUL) and soil water dynamics. Furthermore, we compared gains and losses of forest carbon with reductions in fossil-fuel emissions that result from using harvested biomass for energy production. WTH negatively affected stand growth, biomass, and soil carbon stock; negative effects on growth and biomass can be reduced by leaving nitrogen-rich needles behind during WTH. In a changed climate, organic-matter decomposition and nitrogen mineralization accelerated and tree growth was enhanced, increasing the carbon stock of trees and slightly decreasing the soil carbon stock. In the changed climate, WTH had less influence on forest growth and a similar influence on soil carbon sequestration than in the current climate. In the current climate, the WTH decreased the forest carbon stock by, on average, 26.8 Mg C.ha(-1) over the rotation period. If harvested forest residues are used for energy production instead of fossil fuels, emissions decline by 19 Mg C.ha(-1) (when WTH is applied over a rotation period). Thus, our analysis suggests that using forest residues for energy production leads to a net increase in carbon emissions.
Keywords: carbon sequestration; climate change; bioenergy; nitrogen balance; whole-tree harvesting